OPTICAL PROPERTIES OF ANODIC TITANIA AND IT'S APPLICATION IN MAXILLOFACIAL SURGERY - E. A. Gvozdovskaya; I. V. Timoshevich; K. A. Korzun; S. K. Lazarouk; O. V. Kupreeva; D. V. Isaev; F. A. Gorbacheu; A. S. Lastovka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Studying of anodic titania formation has showen that anodization forming factor at low anodic voltages is 3,3 nm/V, while at high anodic voltages it’s value decreases till 1,5 nm/V. The investigation of optical properties of anodic titania has showed the possibilities to tune the titania refractory index in the whole visible ranges. The application of anodic titania in maxillofacial surgery has been demonstrated for visualization of titanium objects.